Factors affecting investors demand in a real property: A case of residential property in KL and JB / Erny Marliza Abd Muhalip - Abd Muhalip, Erny MarIiza (2008)
Real property is a legal term encompassing real estate and ownership interests in real estate (immovable property). It is a type of property differentiated from personal property. This paper attempts to explain the motivations and take a sample of residential real property investors in Kuala Lumpur (KL) and Johor Bahru (JB) in terms of the behavioral assumption of bounded rationality investment. This paper attempts to explain the motivations and the factors influence of residential rental property investors in KL and JB. All the data for residential property are taking from website of Valuation and Property Services Department at NAPIC from QI year 2002 until Q4 year 2006. This empirical study was used time series multiple regression method to see the relationship of dependent and independent variables. Investors demand in a real property as a dependent variable while the independent variables are rental income, appreciation of value and inflation rate. Qualitative analysis overlays the quantitative data in this research paper, to enable better exploration of the constraints within which individual investors operate via the real property. The results that come out from multiple regression tool analyses indicate only appreciation of value influence the investors demand in real property. However, rental income and inflation rate are not significant to influence investor demand in a real property especially in residential.